Cathodic Electrodeposition of Cerium-Based Conversion Coatings Using Deep Eutectic Solvents Formulations for Corrosion Protection of AA7075 Aluminum Alloys - Aurora Petica; Stefania Costovici; Adrian-Cristian Manea; Anca Cojocaru; Calin Constantin Moise; Sabrina State; Liana Anicai; Marius Enachescu (Metals)
The paper presents a new approach towards forming Ce-based nanostructures using deep eutectic solvents (DESs) as new green solvents and large-scale media for the chemical and electrochemical synthesis of advanced functional surfaces and nanomaterials. Some experimental results regarding the cathodic electrodeposition of cerium-based conversion coatings onto AA7075 aluminum alloys involving different DES-based formulations are discussed. Electrolytes containing Ce(NO3)3·6H2O dissolved in choline chloride-glycerine and choline chloride-urea (1:2 molar ratio) eutectic mixtures with additions of H2O2 have been proposed and investigated. The influence of the operating parameters, including the applied current density, process duration and temperature on the quality of the formed Ce-containing conversion layers was studied. Adherent and uniform Ce-based conversion layers containing 0.3–5 wt.%. Ce have been obtained onto Al alloy substrates. Higher values of the applied current density and longer process durations led to higher Ce content when a choline chloride-urea eutectic mixture was used. Several accelerated corrosion tests were performed to evaluate the corrosion performance, respectively: (i) continuous immersion in 0.5 M NaCl for 720 h with intermediary visual examinations, recording of (ii) potentiodynamic polarization curves and of (iii) impedance spectra at open circuit potential in 0.5 M NaCl, as well as (iv) salt mist test for 240 h. The influence of an additional post-treatment step consisting in the electrochemical deposition of a hydrophobic Ce-based layer involving ethanolic solutions of stearic acid and cerium nitrate is also considered. Different corrosion performances are discussed, taking into account the used DES-based systems and electrodeposition parameters.